2015
DOI: 10.3892/etm.2015.2792
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute exercise on liver function and blood redox status in heavy drinkers

Abstract: Excessive alcohol consumption can induce oxidative stress, resulting in the development of several diseases. Exercise has been reported to prevent and/or improve a number of health issues through several mechanisms, including an improvement in redox status. It has also been previously suggested that exercise can help individuals with alcohol use disorders reduce their alcohol intake; however, research in this field is limited. The aim of the present study was to investigage the effects of acute exercise of mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…There was no evidence that exercise improved heart rate, anxiety or self-efficacy (see table 1). Smoking status was indicated in three studies,15 44 54 but associations between smoking and study outcomes were not reported. Forest plots for the secondary study outcomes are available as online supplementary material.…”
Section: Meta-analysis Of Exercise Versus Control Conditionsmentioning
confidence: 99%
“…There was no evidence that exercise improved heart rate, anxiety or self-efficacy (see table 1). Smoking status was indicated in three studies,15 44 54 but associations between smoking and study outcomes were not reported. Forest plots for the secondary study outcomes are available as online supplementary material.…”
Section: Meta-analysis Of Exercise Versus Control Conditionsmentioning
confidence: 99%
“…The total antioxidant capacity was measured as in Georgakouli et al [15], using 20 µL saliva, 480 µL sodium-potassium phosphate (10 mM, pH 7.4) and 500 µL 2,2-diphenyl-1-picrylhydrazyl (DPPH, 0.1 mM), incubated in the dark for 30 min and centrifuged for 3 min at 20,000 × g. The absorbance A c was read at 520 nm and compared with A 0 , absorbance of a reference sample containing only 20 µL water, DPPH and buffer. Percentage reduction of the DPPH (Q) was defined by Q = 100(A 0 -A c )/A 0 [16].…”
Section: Total Antioxidant Capacitymentioning
confidence: 99%
“…An increase of antioxidant capacity postexercise has been reported in both in healthy individuals and in heavy drinkers [21,22]. However, acute strenuous exercise leads to an increase of oxidative stress and could possibly be damaging, while regular training has protective effects, stimulating the endogenous antioxidant systems [17,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…The aminotransferases' elevation was maintained for at least a week post-exercise, the effects of training depending on the type and intensity of the exercise, the fitness level and gender of the subject [22,23]. It was reported that the increase is higher and more rapid for AST than ALT and AST/ALT ratio higher than 1 for one week post exercise, then returns to normal [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation